2016
DOI: 10.1213/ane.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Electroencephalogram Suppression Predicts Postoperative Delirium

Abstract: Background Postoperative delirium is a common complication associated increased morbidity and mortality, longer hospital stays, and higher healthcare expenditures. Intraoperative electroencephalogram (EEG) slowing has previously been associated with postoperative delirium, but the relationship between intraoperative EEG suppression and postoperative delirium has not been investigated. Methods In this observational cohort study, 727 adult patients receiving general anesthesia with planned intensive care unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 252 publications
(175 citation statements)
references
References 35 publications
6
168
1
Order By: Relevance
“…However, our observations are consistent with the findings of several previous studies [10,[44][45][46], which have demonstrated that hypoactive delirium is the most prevalent delirium subtype, while also the most often underdiagnosed. Hypoactive delirium is more common in the elderly and associated with worse outcomes [43,45], so early detection is paramount to improve perioperative patient care.…”
Section: Limitations Of the Studysupporting
confidence: 93%
“…However, our observations are consistent with the findings of several previous studies [10,[44][45][46], which have demonstrated that hypoactive delirium is the most prevalent delirium subtype, while also the most often underdiagnosed. Hypoactive delirium is more common in the elderly and associated with worse outcomes [43,45], so early detection is paramount to improve perioperative patient care.…”
Section: Limitations Of the Studysupporting
confidence: 93%
“…Recently, it has been proposed that deep anesthetic depth contributes to an increased rate of postoperative delirium. 4346 However, the mechanism of this deep anesthesia effect has not been completely elucidated despite a recent report that burst suppression on electroencephalogram indicative of deep anesthesia may have been the etiologic factor. 46 …”
Section: Discussionmentioning
confidence: 99%
“…3 These patients also incur greater healthcare costs in the year following surgery and report decreased ability to complete activities of daily living 30 days after surgery. 4,5 The pathophysiology of delirium is complex and obscure, and the aetiology is typically multifactorial, with patient vulnerability (e.g. older age), physiological perturbation (e.g.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…12 Two recent observational studies, including one conducted by our group, have identified an association between longer duration of intraoperative electroencephalogram suppression and postoperative delirium. 5,13 However, it is unclear whether the observed associations indicate that increased exposure to anaesthetic agents cause delirium or if underlying patient characteristics increase the risk both for electroencephalogram suppression and for postoperative delirium. Interestingly, some studies have also reported lowerdnot higherdaverage end-tidal concentration of volatile anaesthetic agent as a risk factor for postoperative delirium.…”
Section: Editor's Key Pointsmentioning
confidence: 99%